Investigating Students’ Proficiency and Challenges in Writing Recount Texts: Students’ Perception - Aulia, Devi Shinta Fatma; Soraya, Irma; Siswandari, Dyah (ICONELT, 2024)
This study investigates the proficiency of tenth-grade students at SMA Negeri 10 Surabaya in writing recount texts, focusing on four key indicators: organization, vocabulary, grammar, and mechanics. The research employs a descriptive qualitative method to analyze students’ writing tasks based on criteria from Megawati and Mirjam. The findings reveal that students excel in organization and mechanics, with mean scores of 24 and 11, respectively, both classified as ’Good.’ However, vocabulary and grammar were identified as areas needing significant improvement, with mean scores of 14 and 18, categorized as ’Fair.’ The study highlights that while students effectively structure their texts and manage mechanics well, they face challenges in grammar, particularly with past tense usage and in vocabulary, impacting their ability to convey ideas clearly. Questionnaire data supports these findings, showing that while 85% of students enjoy writing recount texts, 30% encounter difficulties related to coherence and language use. Addressing these issues through targeted grammar and vocabulary instruction is crucial for enhancing overall writing quality. The study aims to inform pedagogical practices and improve students’ proficiency in writing recount texts.